Spousal violence and its determinants among married adolescent girls in Upper Egypt - Amira F. El-Gazzar; Mirette M. Aziz; Heba M. Mohammed; Omaima Elgibaly; Manal M. Darwish (SpringerOpen, 2020)
Abstract Introduction In Egypt, many girls are still married before the age of 18, which is a fundamental violation of the girls' human rights. Early marriage is associated with an alarmingly elevated risk of all types of intimate partner violence that have various negative consequences. The purpose of this study was to identify the predictors of exposure to spousal violence among the early married girls in rural Upper Egypt. Methods A household survey was carried out and covered 23 villages in Assiut and Sohag governorates reaching to a sample of 729 married girls before the age of 20. Listing and enumeration of 4 districts was done to identify the study participants. Data was collected by personal interviews using a structured questionnaire. Bivariate and stepwise regression analyses were performed to identify the predictors of exposure to spousal violence. Results It was found that 15.2% of the study participants were exposed to physical violence while 17.8% were exposed to sexual violence and 7.3% were exposed to both types. Girls married before the age of 18 were more exposed to spousal violence. Stepwise regression analysis found that girls' acceptance to get married was a protective factor against exposure to physical (β = − 1.07, OR 0.34) and sexual (β = − 0.68, OR 0.51) violence. The perceived attitude of husbands and mothers-in-law about considering wife beating "a husband's right" was found to be a risk factor of exposure to physical and sexual violence. Longer duration till the first pregnancy was also associated with more exposure to sexual violence (β = 0.04, OR 1.04). Conclusion Married adolescent girls (MAGs) are highly exposed to physical and sexual violence. This is mainly due to ignoring girls' preference to postpone their marriage, cultural concepts of accepting violence against women, and low sexual satisfaction. This study shows that most determinants of spousal violence were related to culture issues. Identifying these determinants is required to combat such a crucial public health problem that has serious consequences on adolescent health.